2017
DOI: 10.1038/s41598-017-11489-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of liver disease in HIV-infected children and adolescents

Abstract: Liver disease in HIV-infected patients may result from the infection itself, antiretroviral treatment or comorbidities. In this study, we analysed liver disease in 79 HIV-infected children and adolescents aged 14.0 ± 5.1 years. All the patients were receiving combination antiretroviral therapy (cART), with a mean duration of 11.5 ± 4.7 years. Six patients (8%) had detectable HIV viral load, and 8/79 (10%) of the participants were coinfected with hepatitis B or C virus (HCV, 6/8 or HBV, 2/8). Liver disease was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 31 publications
3
26
2
3
Order By: Relevance
“…They can also lead to organ failure, resulting in increased mortality and morbidity and a lower quality of life . Our finding that a quarter of the children had an abnormal liver enzyme test at enrolment is similar to findings from previous studies .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…They can also lead to organ failure, resulting in increased mortality and morbidity and a lower quality of life . Our finding that a quarter of the children had an abnormal liver enzyme test at enrolment is similar to findings from previous studies .…”
Section: Discussionsupporting
confidence: 91%
“…They can also lead to organ failure, resulting in increased mortality and morbidity and a lower quality of life [32]. Our finding that a quarter of the children had an abnormal liver enzyme test at enrolment is similar to findings from previous studies [5,10]. Studies have reported that TDF-containing regimens are associated with renal function abnormalities, including persistent renal disease (PRD) [33][34][35][36].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A high prevalence (32.6%) was also found in Thailand among young people perinatally infected with HIV (mean age 14 years) . Prevalence was lower (~2%) among samples in India, Malawi, Poland, Spain and the United States, among HIV‐positive paediatric patients. Prevalence was higher in Benin (9.6%), Rwanda (6.8%), Tanzania (7%) and Zambia (10.4%) among children <16 years recruited through HIV clinics .…”
Section: Resultsmentioning
confidence: 94%
“…Aspartate aminotransferase (AST) and platelet count were measured using the Architect c8000 (Abbott Laboratories, USA) and ABX Pentra XL80 (Horiba, Japan), respectively, for Aspartate aminotransferase to platelet ratio (APRI) scores calculations. An APRI score > 0.5 was suggestive of liver damage [18,19].…”
Section: Liver Health Assessmentmentioning
confidence: 99%